2008
DOI: 10.1016/j.scitotenv.2008.05.046
|View full text |Cite
|
Sign up to set email alerts
|

A two-year field study with transgenic Bacillus thuringiensis maize: Effects on soil microorganisms

Abstract: We evaluated the changes of some soil microbiological characteristics due to the use of transgenic maize expressing Bacillus thuringiensis (Bt) toxin. A two-year field experiment was conducted (2003 and 2004). Two lines of transgenic Bt maize that express the Cry1Ab protein (event 176 and MON 810) and their near-isogenic non-Bt lines were used. Rhizosphere and non-rhizosphere soils were collected and measurements were performed during the maize cultural cycle and immediately at pre-harvest. Key soil microbiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 50 publications
2
29
0
2
Order By: Relevance
“…Such observations may explain why, in our study, the Bt (Cry1Ab) trait had no effects on MBC, ␤-glucosidase enzyme activity, or bacterial functional diversity in any year when Bt corn was grown in monoculture. Similar results, or small and inconsistent effects, have also been reported in other field studies (Fang et al, 2005;Griffiths et al, 2005;Oliveira et al, 2008). However, shifts in the functional community structures of bacteria were observed in Bt corn rhizosphere in 2003 and, to a lesser extent, in bulk soil in 2007.…”
Section: Bt Trait Effectssupporting
confidence: 88%
See 1 more Smart Citation
“…Such observations may explain why, in our study, the Bt (Cry1Ab) trait had no effects on MBC, ␤-glucosidase enzyme activity, or bacterial functional diversity in any year when Bt corn was grown in monoculture. Similar results, or small and inconsistent effects, have also been reported in other field studies (Fang et al, 2005;Griffiths et al, 2005;Oliveira et al, 2008). However, shifts in the functional community structures of bacteria were observed in Bt corn rhizosphere in 2003 and, to a lesser extent, in bulk soil in 2007.…”
Section: Bt Trait Effectssupporting
confidence: 88%
“…The studies reviewed above explain why most investigations on the effects of Bt cropping systems on soil microorganisms have reported no effects (Oliveira et al, 2008;Liu et al, 2008), minor and transient effects (Devare et al, 2007), or inconsistent effects (Griffiths et al, 2005). When assessing the effects of Bt technology on the soil environment, it is important to weigh the effects of the Bt trait vs. the effects of applying the insecticides (the best management practice) that the Bt technology replaces, i.e., to check if the effects of using a Bt crop are worse than those of applying insecticides to a non-Bt crop.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have reported that the cultivation of herbicideresistant crops hosts microbial communities that differ from those found with non-transgenic varieties (Siciliano and Germida 1999;Dunfield and Germida 2001;Gyamfi et al 2002). However, many other studies also showed that the temporal variability or plant growth stage affects the microbial composition whereas the effects of transgenic crops are minor or absent (Cowgill et al 2002;Dunfield and Germida 2003;Devare et al 2004;Griffiths et al 2006Griffiths et al , 2007Devare et al 2007;Liu et al 2008;Oliveira et al 2008;van Overbeek and van Elsas 2008;Hannula et al 2010). As yet, no studies have been made on how the composition of a soil microbial community might be influenced by transgenic crops resistant to protoporphyrin oxidase-inhibiting herbicides.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the research to date examining the impact of Bt maize on bacteria has focused on soil microbiota and has found no effects of the Bt maize-derived Cry1Ab protein (37,45).…”
mentioning
confidence: 99%